2020
DOI: 10.1371/journal.pcbi.1007590
|View full text |Cite
|
Sign up to set email alerts
|

A single reaction-diffusion equation for the multifarious eruptions of urticaria

Abstract: Urticaria is a common skin disorder characterized by the rapid appearance and disappearance of local skin edema and flares with itching. It is characterized by various macroscopic skin eruptions unique to patients and/or subtypes of urticaria with respect to shape, size, color, and/or duration of eruptions. Nevertheless, the mechanism underlying multifarious eruptions in urticaria is largely unknown. The eruptions are believed to be evoked by histamine release from mast cells in the skin. However, the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 39 publications
(64 reference statements)
3
24
0
1
Order By: Relevance
“…In pathological skin showing expansion, inflammatory response persists and the concentration of mediators fails to return to the original level [ 10 13 ]. Recent theoretical studies have shown two independent mechanisms of how the pathological inflammatory response causes expansion [ 14 , 15 ]. One is the diffusion of inflammatory mediators and the other is positive feedback, which can generate bistability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In pathological skin showing expansion, inflammatory response persists and the concentration of mediators fails to return to the original level [ 10 13 ]. Recent theoretical studies have shown two independent mechanisms of how the pathological inflammatory response causes expansion [ 14 , 15 ]. One is the diffusion of inflammatory mediators and the other is positive feedback, which can generate bistability.…”
Section: Discussionmentioning
confidence: 99%
“…Expansion occurs when S T is closer to S NI than to S I , whereas shrinkage occurs when S T is closer to S I than to S NI in a wide range of parameters controlling the inflammatory response, including positive feedback, basal secretion, and degradation ( Fig 4 ; S3 Fig in S1 Appendix ). An interesting future study would be the analysis of whether the balance captures such inflammatory wave dynamics in other bistable systems, with more complex biochemical reactions [ 12 , 14 , 15 ]. Therefore, the balance of bistable states could provide an experimentally testable framework for the normal and pathological inflammatory responses ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Las señales que activan a los mastocitos aún no están definidas del todo, pero se cree que estos no solo responden a alérgenos que entran en contacto con las moléculas de IgE de su superficie, sino que también responden a estímulos como superantígenos, neuropéptidos, anticuerpos, agentes físicos, adenosín trifosfato (ATP), anafilotoxinas y agentes químicos. 10,11,12 La histamina y otros mediadores como el factor activador de plaquetas (PAF), factor de necrosis tumoral alfa (TNF-α), interleucinas (IL) 3, 4, 5, 6, 8, 13 determinan el desarrollo temprano de la inflamación, induciendo la activación de neuropéptidos (sustancia P, endorfinas, encefalinas) por las terminaciones nerviosas, vasodilatación, extravasación de plasma y reclutamiento de células inflamatorias; causando prurito, ardor y las lesiones clásicas de urticaria, ronchas. 9,10 Las células inflamatorias recién involucradas en este proceso secretan mediadores inflamatorios, intensificándose y prolongando la respuesta inflamatoria.…”
Section: Etiologíaunclassified
“…Urticaria is a localized edema response caused by the expansion of cutaneous small blood vessels and mucous membranes and increased permeability with the activation of mast cells as the core. [ 1 3 ] It is often accompanied by wind masses of varying sizes, itching, and angioedema. According to the statistics of the World Allergy Organization, about 20% of people have had urticaria during their lifetime.…”
Section: Introductionmentioning
confidence: 99%